Zygmunt Bauman’s Ethical Warnings in the Area of Economics. The Third Millennium’s Perspective - Matera, Rafał (Annales. Etyka w Życiu Gospodarczym, 2014)
Zygmunt Bauman is not only a sociologist and philosopher reputable in the world of science, he is also a father figure for people interested in the phenomenon of globalization. Bauman investigates how current economic and political changes influence the lives of particular societies. It was important to underline that also economists can make use of Bauman’s ideas but with a few reservations That is why the following crucial areas were proposed relating to economic aspects: the meaning of consumptionism and wastage; global inequalities; the reasons and consequences of the global economic crisis, and some heterodox matters such as happiness, welfare, and well-being, all of which can be helpful in understanding the multidimensional globalization process.